RXFP1 Receptor Activation by Relaxin-2 Induces Vascular Relaxation in Mice via a Gαi2-Protein/PI3Kß/γ/Nitric Oxide-Coupled Pathway - Lian, Xiaoming; Beer-Hammer, Sandra; König, Gabriele M.; Kostenis, Evi; Nürnberg, Bernd; Gollasch, Maik (Frontiers in Physiology, 2018)
Background: Relaxins are small peptide hormones, which are novel candidate molecules that play important roles in cardiometablic syndrome. Relaxins are structurally related to the insulin hormone superfamily, which provide vasodilatory effects by activation of G-protein-coupled relaxin receptors (RXFPs) and stimulation of endogenous nitric oxide (NO) generation. Recently, relaxin could be demonstrated to activate Gi proteins and phosphoinositide 3-kinase (PI3K) pathways in cultured endothelial cells in vitro. However, the contribution of the Gi-PI3K pathway and their individual components in relaxin-dependent relaxation of intact arteries remains elusive. Methods: We used Gi2- (Gnai2-/-) and Gi3-deficient (Gnai3-/-) mice, pharmacological tools and wire myography to study G-protein-coupled signaling pathways involved in relaxation of mouse isolated mesenteric arteries by relaxins. Human relaxin-1, relaxin-2 and relaxin-3 were tested. Results: Relaxin-2 (~50% relaxation at 10-11 M) was the most potent vasodilatory relaxin in mouse mesenteric arteries, compared to relaxin-1 and relaxin-3. The vasodilatory effects of relaxin-2 were inhibited by removal of the endothelium or treatment of the vessels with N (G)-nitro-L-arginine methyl ester (L-NAME, endothelial nitric oxide synthase (eNOS) inhibitor) or simazine (RXFP1 inhibitor). The vasodilatory effects of relaxin-2 were absent in arteries of mice treated with pertussis toxin (PTX). They were also absent in arteries isolated from Gnai2-/- mice, but not from Gnai3-/- mice. The effects were not affected by FR900359 (Gq protein inhibitor) or PI-103 (PI3Ka inhibitor), but inhibited by TGX-221 (PI3KB inhibitor) or AS-252424 (PI3Kr inhibitor). Simazine did not influence the anti-contractile effect of perivascular adipose tissue. Conclusions: Our data indicate that relaxin-2 produces endothelium- and NO-dependent relaxation of mouse mesenteric arteries by activation of RXFP1 coupled to Gi2-PI3K-eNOS pathway. Targeting vasodilatory Gi-protein-coupled RXFP1 pathways may provide promising opportunities for drug discovery in endothelial dysfunction and cardiometabolic disease.